The Price Impact of Extreme Weather in Developing Countries. Issue 619 (22nd May 2018) - Heinen, Andréas; Khadan, Jeetendra; Strobl, Eric
Abstract: We examine the impact of extreme weather on consumer prices in developing countries by constructing a monthly data set of potential hurricane and flood destruction indices and linking these with consumer price data for 15 Caribbean islands. Our econometric model shows that the price impact of extreme weather events can be large. To illustrate potential welfare losses due to these price effects, we combine our estimates with price elasticities obtained from a demand system and with event probabilities for Jamaica. Our results show that while expected monthly losses are small, rare events can cause large falls in monthly welfare due to price increases.